How developed countries can learn from developing countries to tackle climate change. (March 2020) - Carattini, Stefano; Gosnell, Greer; Tavoni, Alessandro
Abstract: Climate change and global poverty are the most pressing issues of this century. If insufficiently addressed, climate change will exacerbate poverty and inequality within and across nations. Addressing it requires that people in developed and developing countries adopt new behaviors and technologies to reduce their greenhouse gas emissions and to adapt to a changing climate. A major contribution of the 2019 Nobel Laureates consists in providing new tools to advance knowledge on the mechanisms driving the diffusion of non-normative behaviors, by combining social network analysis with field experiments. To inform climate policy, we encourage research that applies this methodological innovation to understand the extent to which diffusion mechanisms may be crucial to accelerate the transition toward greener economies. Scholars working in developed countries have much to learn from recent advances in development economics. We identify fruitful areas for research in the global North.